Treatment of Desquamative Gingivitis with Free Gingival Graft: A Case Report - Mehdi Vatankhah; Mohammad Taghi Chitsazi; Masoumeh Mehdipour; Ali Taghavi Zenouz; Rasoul Estakhri (Tabriz University of Medical Sciences, 2010)
Recalcitrant gingival erythematous lichen planus lesions comprise a considerable therapeutic problem. This case of chronic desquamative gingivitis in a 25-year-old woman with erosive oral lichen planus was treated with topical and systemic corticosteroid administration, followed by placement of a free gingival graft on right upper quadrant. Although recurrence of the lesions was observed following both treatment modalities, free gingival graft despite being an aggressive therapy, proved more effective and with fewer side effects compared with topical or systemic steroid therapy, and seems to be a promising treatment modality with the benefit of more stable results, among others.